Предмет: Математика,
автор: nmoshechkova
Упростите выражение и найдите его значение:
3(2а-4b)+5(3b-6а) при а=0,1 b=-0,3
Ответы
Автор ответа:
0
3(2а - 4b) + 5(3b - 6а) =
6а - 12b + 15b - 30a =
3b - 24a при а = 0,1; b = -0,3
3*(-0,3) - 24*0,1 =
-0,9 - 2,4 = -3,3
6а - 12b + 15b - 30a =
3b - 24a при а = 0,1; b = -0,3
3*(-0,3) - 24*0,1 =
-0,9 - 2,4 = -3,3
Автор ответа:
0
спасибо)
Похожие вопросы
Предмет: Алгебра,
автор: 6vklass00
Предмет: Химия,
автор: xxxeniaaa
Предмет: Математика,
автор: daniilsavelev09
Предмет: Математика,
автор: Аноним